Implementation of Blood‐Based Biomarker Assays to Deliver Consistent and Comparable Data. (20th December 2022) - Russ, Kristen A; Stecker, Mara; Olson, Chelsea; Foroud, Tatiana M.; Dage, Jeffrey L.
Abstract: Background: Implementing biomarkers for Alzheimer's Disease (AD) is an important area of research that will enhance the ability to accurately characterize the disease with the goal of earlier detection and treatment. Analytical validation is the first step to determine the measuring range, specificity, precision, and matrix effects of biomarker assays. Studies on analyte stability and performance bridging when key reagents are changed are critical to deliver reliable and consistent data over time. The goal of these studies is to demonstrate the performance of the assays implemented in the NCRAD Biomarker Assay Laboratory (BAL). Method: Samples were collected from patients with AD (N=14) and from healthy control subjects (N=19) by the Indiana Biobank. Samples were assayed on the Quanterix Simoa HD‐X platform using the Simoa Nf‐light Advantage Kit and P‐tau181v2 Advantage Kit to determine neurofilament light chain and P‐tau 181 concentrations. Five samples were chosen to span high, medium, and low concentrations for the validation method. Sets of 3 plates were run on two separate days using kits of the same lot number and same 5 samples. Validation assessed precision, parallelism, protein recovery, dilutional linearity, and sensitivity. In addition, our validation method allowed assessment of intra and inter batch variability. Euroimmun Beta‐Amyloid 1‐40 and 1‐42 ELISA kits were also assessed. Result: The Nf‐Light Advantage Kit precision data coefficient of variation (CV) was less than 7% within plates and less than 8% percent within batches. The CV for precision between the runs on both days was less than 10%. The P‐tau181v2 Advantage assay precision data CV was less than 7% within plates and less than 10% within batches. The CV for total precision between runs on both days was less than 10%. Dilutional linearity, protein recovery, sensitivity, and parallelism were within acceptable levels. Conclusion: The validation studies of the commercially available Simoa Nf‐light and P‐tau181v2 Advantage Kits demonstrate the performance of these assays as implemented within the NCRAD BAL. The stability and bridging studies illustrate how the assays will be kept performing over time to deliver consistent and reliable data for researchers submitting samples for analysis. Supported by U24 AG021886 and UL1TR002529.